2006
DOI: 10.2337/db05-1511
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Toxicity Is Responsible for the Development of Impaired Regulation of Endogenous Glucose Production and Hepatic Glucokinase in Zucker Diabetic Fatty Rats

Abstract: The effect of restoration of normoglycemia by a novel sodium-dependent glucose transporter inhibitor (T-1095) on impaired hepatic glucose uptake was examined in 14-week-old Zucker diabetic fatty (ZDF) rats. The nontreated group exhibited persistent endogenous glucose production (EGP) despite marked hyperglycemia. Gluconeogenesis and glucose cycling (GC) were responsible for 46 and 51% of glucose-6-phosphatase (G6Pase) flux, respectively. Net incorporation of plasma glucose into hepatic glycogen was negligible.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 69 publications
3
37
0
Order By: Relevance
“…Previous studies have shown that glucose-induced translocation of glucokinase from the nucleus to the cytoplasm is impaired in models of insulin resistance and diabetes such as the Goto-Kakizaki, OLETF (41), and Zucker diabetic fatty rats (20,21). However, the underlying mechanisms have not been determined.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have shown that glucose-induced translocation of glucokinase from the nucleus to the cytoplasm is impaired in models of insulin resistance and diabetes such as the Goto-Kakizaki, OLETF (41), and Zucker diabetic fatty rats (20,21). However, the underlying mechanisms have not been determined.…”
Section: Discussionmentioning
confidence: 92%
“…Defects in glucokinase translocation have been reported in animal models of Type 2 diabetes, including the Goto-Kakizaki rat and the Otsuka Long Evans Tokushima Fatty (OLETF) rat (41) and the Zucker diabetic fatty rat (20,21). The Zucker diabetic rat had impaired glucokinase translocation during a glucose and insulin infusion (21).…”
mentioning
confidence: 99%
“…The SA (dpm/mol) of plasma [2-3 H]-and [3-3 H]glucose were determined as described previously (24). Plasma samples were deproteinized using Ba(OH)2 and ZnSO4.…”
Section: Methodsmentioning
confidence: 99%
“…In the liver, the immunostaining for GK and GKRP expression, along with the Western blot analyses of these proteins, was performed using sheep anti-rat GST-GK serum and rabbit anti-rat GST-GKRP serum, as reported previously (13,23,24). Quantitative image analysis of GK and GKRP immunofluorescence in the nucleus and cytoplasm of hepatocytes was performed using a Zeiss LSM510 confocal laser scanning microscope (13,23,24). The internal He/Ne laser and external argon-krypton laser at 543, 647, and 488 nm were used to optimally excite Cy3, Cy5, and YoPro-1 fluorescence, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation